2013
DOI: 10.4025/actascibiolsci.v35i2.13334
|View full text |Cite
|
Sign up to set email alerts
|

Study on the development of frontal sinuses by morphometric analysis of the skull

Abstract: The frontal sinuses are cranial areas of clinical, forensic and pathology importance whose development mechanisms are still poorly defined. Nasal airflow and brain development are two of the main theories. Current analysis debates whether they are the real determinants of frontal sinuses growth, which may be proved by the skull's morphometric analysis. Four groups of measures related to the external cranial architecture, the pyriform aperture, orbital cavities and frontal sinuses were defined. Thirty-three sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Filho et al also found a relationship between nasal pyriform aperture area and left FSV ( r = 0.435, P = .011) and reported that the degree of nasal cavity aeration affects FS development. 10 In this study, there appears to be a positive linear relationship between nasal height and frontal morphometry. In addition, the effect of nasal height is more apparent than maximum skull length for most of the analyses.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…Filho et al also found a relationship between nasal pyriform aperture area and left FSV ( r = 0.435, P = .011) and reported that the degree of nasal cavity aeration affects FS development. 10 In this study, there appears to be a positive linear relationship between nasal height and frontal morphometry. In addition, the effect of nasal height is more apparent than maximum skull length for most of the analyses.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies have suggested that FSs are larger in brachiocephalic heads than dolichocephalic heads. 10 Filho et al found a relationship of spin bregmatic distance and glabellalambda curvature with left FSV (r ¼ 0.450, P ¼ .009 and r ¼ 0.433, P ¼ .012, respectively). 10 In another report by Tehranchi et al, a recent study that utilized a weak methodology, they showed a correlation between FS dimensions and anterior facial height in males and increased gonial angle in females.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations